The role of green innovation in reducing carbon emissions: A case study analysis of Algeria during the period 1990–2023 SAIDI Mohamed - Mohamed SAIDI (Journal of Excellence for Economics and Management Research, 2026)
This study aims to analyze the impact of green innovation on carbon dioxide emissions in Algeria during the period 1990–2023 using the ARDL model, incorporating variables including research and development, trade liberalization, renewable energy, and urbanization. The results showed a significant inverse relationship between green innovation and emissions, with green innovation contributing to a 2.40% reduction in the short term and a 2.78% reduction in the long term, confirming the effectiveness of environmentally friendly technologies. Furthermore, spending on research and development significantly reduces emissions, reflecting the importance of investing in innovation. In contrast, neither trade liberalization nor renewable energy showed a significant impact, which is related to the specific characteristics of the Algerian economy and its limited reliance on clean energy. Urbanization had an insignificant impact in the short term but a positive and significant impact in the long term, indicating its role in increasing emissions